In Search of Common Ground: One Pragmatist Perspective on the Debate Over Contract Surrogacy - Baughman, Matthew H. (Columbia Journal of Gender and Law, 2001)
Two events prompted my interest in the topic of this article. The first was the Baby ‘M’ case in which the New Jersey Supreme Court found a surrogacy contract between an infertile couple and a woman who agreed to be artificially impregnated for money to be void in violation of the law and public policy of the state. When I first learned of the decision, I accepted it as largely unproblematic. The contract seemed like an obvious attempt by a wealthy couple to coerce a poor and desperate woman into selling her body for sustenance. The second event occurred ten years after the Baby ‘M’ case when Richard Posner delivered his wildly provocative essay on normative moral theory at the 1997-98 Holmes Lectures at Harvard Law School. In The Problematics of Moral and Legal Theory, Posner confessed his “visceral dislike . . . of academic moralism,” while at the same time presenting a fairly channeled (though casually “Posnerian”), poststructuralist argument against the foundationalist Moral Realism of the kind exhibited by Ronald Dworkin, Thomas Nagel, Martha Nussbaum, and many others.